Evaluasi Program Penanggulangan ISPA di Puskemas Sikumana - Serlie K.A. Littik; Elnike Putri Dju Nina; Rina Waty Sirait (Yayasan Literasi Sains Indonesia, 2025)
Acute respiratory infections are the leading cause of morbidity and mortality from infectious diseases in the world. ARI is the most common disease in outpatients at Puskesmas Sikumana, Kupang City with a percentage of 43%, in 2023. The purpose of this study was to determine the evaluation of the ARI Management Program at Puskesmas Sikumana. This research is a qualitative research that produces descriptive data in the form of descriptions and written or spoken words from information and observedbehavior. The selection of informants in this study was carried out using purposive sampling method. The results showed that the Input variable showed that there were 5 health workers involved in the ARI program, facilities and infrastructure supporting ARI in the Puskesmas Sikumana working area were less equipped with ventilator facilities but there was routine maintenance and care. In the process variable, the preparation of the program plan is carried out by the planning team at the Puskesmas every year. There is also a way to determine the status of people with ARI. In addition, there is monitoring of the ARI prevention program which is carried out every 3 months and there is mandatory recording and reporting every month and every year. The Output variable shows that there are strategies so that the program is right on target. In the implementation of the program, there are factors that influence. To improve the human resources of health workers at the Puskesmas, special training is always held to improve the human resources of health workers. The conclusion of this research is that inadequate input affects the process so that the output of ARI disease management at Puskesmas Sikumana has not achieved success. Facilities and infrastructure should be provided, especially ventilators to support the implementation of the ARI program.